Much Ado about nothing? Interest and non-interest products and services: Their impact on small banks’ margins - Fredriksson, Antti; Maresch, Daniela; Moro, Andrea (Cogent OA, 2017)
We investigate the impact of interest and non-interest products and services on the margin a bank can derive from a specific customer. The analysis is based on 4,277 observations of relationships between small cooperative banks and small and medium-sized enterprises (SME) in Finland from 2001 to 2005. The results show that only long-term loans significantly contribute to the bank’s margin, whereas short-term loans as well as other additional products and services do not affect the bank’s margin, and cash management services even seem to reduce the bank’s margin. The findings suggest that small cooperative banks did concentrate on their core business during the first years of this millennium, i.e. lending, instead of diversifying their activities to increase their margin. However, by taking only financial considerations into account, small cooperative banks might forget about the non-financial impacts of their decisions, which may involve a considerable loss of information about SMEs.
Keywords: Bank profitability; Product diversification; Lending; Small banks; Small firms